Communication without borders: Selected Papers of the International Conference Languages 2011: X Meeting of Aprolínguas and II Meeting of ReCLes.pt - Arau Ribeiro, Maria del Carmen (2018)
This publication is the result of the selected papers presented at Languages 2011: Communication without borders, the X Meeting of Aprolíngu@s and the II Meeting of ReCLes.pt, respectively the Associação Portuguesa de Professores de Línguas Estrangeiras no Ensino Superior (Aprolíngu@s – the Portuguese Association of Foreign Language Teachers in Higher Education) and the Associação de Centros de Línguas no Ensinos Superior em Portugal (ReCLes.pt – the Network Association of Language Centres in Higher Education in Portugal). In their second annual collaborative effort, the Executive Boards of ReCLes.pt and Aprolíngu@s, both led by the Escola Superior de Tecnologia e Gestão (ESTG – School of Management and Technology) of the Instituto Politécnico da Guarda (IPG –Polytechnic Institute of Guarda), joined with the Escola Superior de Educação of the Instituto Politécnico de Bragança (ESEB – School of Education at the Polytechnic Institute of Bragança) to promote the articulation of research in foreign language teaching in higher education both nationally and internationally. Immediately following the first International Meeting of ReCLes.pt, the Association of Language Centers in Higher Education in Portugal, in 2010 at the School of Technology & Management of the Polytechnic Institute of Guarda, held in collaboration with and support from the X International Meeting of Aprolínguas, the Portuguese Association of Foreign Language Teachers in Higher Education, our member representative Isabel Chumbo brought an invitation to hold the II International Meeting of ReCLes.pt in cooperation with the Language Center of the School of Education at the Polytechnic Institute of Bragança. ReCLes.pt was keen to accept the offer, particularly due to the border setting of the school, nearly nestled into Spain in the northeast corner of Portugal.